Allogeneic hematopoietic cell transplantation in adult patients with myelodysplastic/myeloproliferative neoplasms - Lim, Sung-Nam (Korean Society of Hematology; Korean Society of Blood and Marrow Transplantation; Korean Society of Pediatric Hematology-Oncology; Korean Society on Thrombosis and Hemostasis, 2013)
BACKGROUND: In adults, the 2 main types of myelodysplastic/myeloproliferative neoplasms (MDS/MPN) are chronic myelomonocytic leukemia (CMML) and atypical chronic myeloid leukemia (aCML). Both are associated with a poor prognosis. Allogeneic hematopoietic cell transplantation (HCT) is the only known curative treatment modality for these diseases, but data on outcomes following such treatment are limited. We analyzed the outcomes of patients with MDS/MPN after allogeneic HCT. METHODS: This retrospective study included 10 patients with MDS/MPN who received allogeneic HCT at Asan Medical Center from 2002 to 2010. Of these 10 patients, 7 had CMML, 2 had aCML, and 1 had unclassifiable MDS/MPN. Five patients received a myeloablative conditioning (MAC) regimen (busulfan-cyclophosphamide), and 5 received reduced-intensity conditioning (RIC) regimen. RESULTS: Neutrophil engraftment was achieved in all patients. After a median follow-up of 47.5 months among surviving patients, 4 had relapsed and 5 had died. There was only 1 treatment-related death. The 5-year rates of overall, relapse-free, and event-free survival were 42.2%, 51.9%, and 46.7%, respectively. Relapse was the leading cause of treatment failure, and all relapses were observed in patients who had received RIC and who did not develop chronic graft-versus-host disease. CONCLUSION: Allogeneic HCT can induce durable remission in patients with MDS/MPN, but RIC cannot replace MAC in patients eligible for myeloablative treatments.